Computed Tomography Scan Findings in Various Modes of Head Injury, using Ge Optima 128 Slice CT Scanner - Nadia Khattak, Muhammad Riaz, Raheel Iqbal, Sana Hussain, Muhammad Jawad, Fayaz Ahmed, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Head injury is a global health problem that can cause disability and may result in death. CT scan detects and precisely localizes the skull fractures, epidural/subdural/subarachnoid hemorrhages, brain contusions and cerebral edema etc. CT has proven to be a valuable tool in the early diagnosis and prompt management of head trauma patients. Methods: A descriptive cross-sectional study, including 380 patients, presented to the radiology department of Hayatabad medical complex witha history of head trauma for computed tomography examination, from October 2019 to October 2020. The nature of the brain and skull lesions was analyzed in our study and the frequency of various findings was recorded. Results: Among 380 patients, the majority were males (248) making the male to female ratio to be around 2:1. The most prevalent finding was skull fractures (23.4%) followed by cerebral contusions (17.1%). Among extra-axial brain hemorrhages, extradural hematoma (15.2%) was observed more than subdural hematoma (6.8%) while only 3.4% presented with subarachnoid hemorrhages which also included intraventricular hemorrhages. Practical Implication: As road traffic accidents are the most common cause of head injuries so road traffic safety measures ought to be strictly enforced. Most of the CT scan done during head injuries were normal so CT guidelines for ordering should be implemented to scale back extra patient irradiation, unnecessary waste of resources Conclusion: Our study concluded that younger populations and males are more prone to head injury and road traffic accident is the most common mode of head trauma. So, ensuring proper traffic rules along with educating the more prone population will significantly reduce the incidence of serious head injuries. Keywords: Head Injury, Computed Tomography (CT), Road Traffic Accidents (RTA), Skull Fractures, Epidural Hematoma.